Promoting Health and Safety on UK Construction Sites Using Lean Construction Strategies - Chaudhari, Himesh; Sarhan, Saad; Abdelmegid, Mohammed; Saad, Ali; Poshdar, Mani (IGLC, 2024)
Poor health and safety (H&S) conditions in the construction industry are linked to ill-defined social and economic factors. To mitigate poor construction H&S performance, it has been widely recommended that Lean Construction (LC) strategies be adopted. Existing literature shows a strong correlation between implementing LC and improving construction H&S performance. However, limited research utilises qualitative research based on primary data to understand the perspectives of experts with real-world experience on the LC/H&S relationship. To address this gap, we conducted a novel study interviewing eight highly experienced LC experts to gain insights into how LC can enhance H&S in construction projects. Going beyond theory, we conceptualised a model linking key LC methods to root causes of H&S accidents to enable tangible improvements. This model intends to guide construction professionals in adopting and implementing LC strategies to foster safer construction workplaces. Our findings affirm and extend prior research by emphasising the efficacy of LC methods in improving H&S performance in construction projects.